Does Geographic Location Affect the Quality of Care? The Difference in Readmission Rates Between the Border and Non-Border Hospitals in Texas - Shin DY; Chang J; Ramamonjiarivelo ZH; Medina M (Dove Medical Press, 2022)
Dong Yeong Shin,1 Jongwha Chang,2 Zo H Ramamonjiarivelo,3 Mar Medina4 1Department of Public Health Sciences, New Mexico State University, Las Cruces, NM, USA; 2Department of Healthcare Administration, College of Business, Texas Woman's University, Denton, TX, USA; 3School of Health Administration, Texas State University, San Marcos, TX, USA; 4School of Pharmacy, University of Texas at El Paso, El Paso, TX, USACorrespondence: Jongwha Chang, Healthcare Administration, College of Business, Texas Woman's University, 304 Administration Dr., Denton, TX, 76204, USA, Email jchang3@twu.eduPurpose: Previous literature has limited empirical evidence describing the association between border location and readmission rates among hospitals in the U.S.-Mexico border region. Thus, our study explores this novel connection in Texas border hospitals using a non-experimental longitudinal study design.Materials and Methods: Using longitudinal panel data (2013∼ 2016) drawn from the American Hospital Association Annual Survey Database, Hospital Compare, and Area Health Resource File, a random-effects linear regression analysis was performed to quantify the impact of border location on the readmission rates of the same sample at multiple timed points.Results: We found a positive relationship between border location and 30-day hospital readmission rates for heart failure and pneumonia in Texas. Border hospitals in Texas had approximately a 4.17% higher heart failure readmission rate and a 3.46% higher pneumonia readmission rate than non-border hospitals. We also identified several hospital organizational and market factors associated (eg, registered nurse [RN]-to-patient ratio) with hospital readmission rates.Conclusion: The results suggest that improving RN staffing levels can be the most feasible action to lower the readmission rates among border Texas hospitals. Decreasing readmission rates by increasing RN staffing levels would also help them avoid reimbursement reduction under the Hospital Readmission Reduction Program (HRRP) and enhance overall health in Texas border communities. Further, to improve border health in Texas, decision-makers in state and local governments must consider incentivizing border hospitals to improve RN staffing levels and modulating the market factors affecting hospital readmission rates that are mostly beyond the control of hospitals.Keywords: U.S.-Mexico border, hospital, quality of care, readmission, registered nurse, nurse staffing, hospital characteristics, Hispanic population, county, market factors